Greatest Challenges of Rectal Cancer Survivors: Results of a Population-Based Survey. Issue 11 (November 2016) - McMullen, Carmit K.; Bulkley, Joanna E.; Altschuler, Andrea; Wendel, Christopher S.; Grant, Marcia; Hornbrook, Mark C.; Sun, Virginia; Krouse, Robert S.
Abstract : BACKGROUND: Eliciting the priorities of cancer survivors is essential to address the specific needs of cancer survivor subgroups. OBJECTIVE: The purpose of this study was to describe the greatest challenges related to treatment for long-term rectal cancer survivors. DESIGN: This was an observational study with a cross-sectional survey. SETTINGS: The study included members of Kaiser Permanente Northern California and Northwest health plans. PATIENTS: A survey was mailed to long-term (≥5 years postdiagnosis) survivors of rectal cancer who had an anastomosis, temporary ostomy, or permanent ostomy. MAIN OUTCOME MEASURES: The main outcome was measured with an open-ended question about the greatest challenge related to cancer surgery. We categorized responses using a grounded theory approach with double coding for reliability. Bonferroni-adjusted χ 2 values were used to assess differences in the proportions of subgroups who mentioned challenges within each response category. RESULTS: The survey completion rate was 61% (577/953); 76% (440/577) of participants responded to the greatest challenge question. The greatest challenges for respondents were bowel/ostomy management (reported by 44%), negative psychosocial effects (37%), late effects of treatment (21%), comorbidities and aging (13%), postoperative recovery (5%), and negative healthcare experiences (5%). Survivors with temporary ostomy or anastomosis were more likely than survivors with permanent ostomy to report late effects ( p < 0.0001 and p = 0.01). Survivors with anastomosis were less likely than survivors with permanent ostomy to report negative psychosocial impacts ( p = 0.0001). LIMITATIONS: Generalizability is restricted by the lack of ethnically and racially diverse, uninsured (non-Medicare–eligible population), and non-English–speaking participants. Because the survey was cross-sectional and included respondents at different times since diagnosis, we could not adequately address changes in the greatest challenges over time. CONCLUSIONS: Our results reveal the need for bowel/ostomy management, psychosocial services, and surveillance for late effects in survivorship and supportive care services for all survivors of rectal cancer, regardless of ostomy status. The perspective of long-term survivors with anastomosis reveals challenges that may not be anticipated during decision making for treatment (see Video, Supplemental Digital Content 1, http://links.lww.com/DCR/A254 ). Abstract : Supplemental Digital Content is available in the text.